Why Indonesia Should Ratify the Biodiversity Beyond National Jurisdiction Agreement? - Aryuni Yuliantiningsih; Noer Indriati; Wismaningsih Wismaningsih; Baginda Khalid Hidayat Jati (Jurnal Dinamika Hukum, 2025)
Indonesia signed the Biodiversity Beyond National Jurisdiction (BBNJ) Agreement in June 2023 but has yet to decide on ratification. This treaty fills legal gaps in UNCLOS 1982 by regulating marine genetic resources (MGRs), marine protected areas (MPAs), environmental impact assessments (EIAs), and equitable benefit-sharing mechanisms in areas beyond national jurisdiction (ABNJ). Given Indonesia’s strategic position as the world’s largest archipelagic state, ratification is essential to align national policies with global commitments, secure access to MGRs, and reinforce Indonesia’s role in international ocean governance. This study employs a doctrinal legal approach to examine Indonesia’s rights and obligations under the BBNJ Agreement and identify necessary adjustments to domestic laws and policies. The findings indicate that delaying ratification weakens Indonesia’s position in ABNJ governance and risks limiting access to MGR-related research, technology transfer, and benefit-sharing opportunities. Immediate ratification would ensure Indonesia’s active participation in global marine conservation while strengthening national legal certainty and maritime diplomacy. Future research should explore legal harmonization strategies to facilitate effective implementation of the agreement.